EFFECT ON CHILDREN PLAY ROOM TYPOLOGY PATTERN PLAY ACTIVITY BEHAVIOR OF CHILDREN CASE STUDY: RUSUNAWA JATINEGARA WEST, EAST JAKARTA AND RUSUNAWA CIGUGUR, CIMAHI, WEST JAVA - Febriyana, Y. Basuki Dwisusanto, Deti (Jurnal Riset Arsitektur, 2017)
Abstract - Fulfilling the ever-increasing need for residential areas in a brief period of time has triggered the remarkable immaturity that can be observed in the development of urban planning. Multi-storied apartments may form a solution for the problem of meeting this demand. However, their design fails to pay sufficient attention to the necessary means of social interaction, especially in providing a suitable area for children’s playgrounds. This study aims to explore the various typologies for children’s playgrounds, and the influence they exert on the pattern of play activities. This research study may stimulate the effort to improve the quality of residential areas and the space reserved for children’s playgrounds, focusing on the low-rent apartments known as rusunawa found in West Jatinegara, East Jakarta and those situated in Cigugur, Cimahi, West Java. In the latter there was no playground available for children, so that the local residents’ children finally created a new spot not originally intended for that purpose, whereas the former had already provided one. The samples selected consist of both boys and girls whose age range is between 2-12 years old. The theoretical background literature deals with home-range, behavioral setting, personal space and children’s play activities. This research study yields the conclusion that the spatial typology does not affect the pattern of the children’s play activities, and furthermore no difference was found in the behavioral pattern of the children’s play activities between the two neighborhoods examined. The behavioral pattern of the children’s play activities turned out to be just the same. Moreover, in both study locations, it was found that the older the children, the more capacious the personal space they require tends to be. Keywords: Spatial Typology, Children’s Play Activities, Home-range, Behavioral Setting